(untitled) (Research, Society and Development, 2024)
The objective of this study was to evaluate milk production and forage production and accumulation in mombaça grass pastures managed at different pre-grazing heights. The design used was randomized blocks, with two entry heights 90 and 80 cm and the same grazing intensity 50%. Forage mass in the pre- and post-grazing condition was measured using five 1 m2 frames in each experimental unit. For the evaluation of the morphological components of the forage, subsamples were taken to determine pre and post-grazing forage masses. Grazing was pasted by 32 lactating F1 cows with an average weight of 550 kg. Mean pre-grazing heights observed were 92.97±5.7 and 81.88±4.6 cm for the 90 and 80 cm entry treatments, respectively. For the post-grazing heights of 45 and 40 cm, 45.75±3.75 and 40.70±3.70 cm were obtained, respectively. Forage productivity on pastures at heights of 80 and 90 cm was 5,822.1 and 7,205.4 kg /ha-1, respectively. On the other hand, dry mass in the pre-grazing condition differed between treatments with a higher value for 90 cm (4,114.5 kg/ha-1) in relation to 80 cm (3,368.1 kg/ha-1). Milk production was 13.2% higher for the lowest height. Mombaça grass pastures can be managed flexibly, with the animals entering and respecting the canopy height range of 80 to 90 cm without harming forage production. Mombaça grass pastures managed with lower pre-grazing heights (80 cm) promote higher milk production.